COWORKING SPACE DESIGN IN MEDAN CITY WITH GREEN ARCHITECTURE CONCEPT - Prayoga, Bagas; Sigit, Faurantia Forlana; Nuraini, Cut (Proceeding International Conference of Science Technology and Social Humanities, 2022)
Designing a Coworking Space with a Green Architecture concept in Medan City is a design project aimed at creating a flexible and environmentally friendly workspace in Medan City. The Green Architecture concept is applied in this design to have a positive impact on the surrounding environment. This Coworking Space has several unique features, such as the use of workspace, private space, and relaxation space. It is expected that this Coworking Space will contribute to the development of businesses and entrepreneurship in Medan City. The design process of this Coworking Space is explained in detail in this article, from the concept to the final design.